2017
DOI: 10.1111/pbr.12543
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of maize lines introduced in the early stages of a breeding programme

Abstract: The diversity analysis and screening of major genes using genomewide association studies (GWAS) for quantitative traits have been exploited in several grass crops, but in maize it has been neglected. This study was conducted to evaluate the genetic diversity of a collection of lines and the potential of genomic analysis as an initial screening tool. For this purpose, a collection of 470 maize inbred lines were genotyped with 23,153 Dart‐seq markers. The genomewide analysis of ear weight was used aiming to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
(136 reference statements)
1
4
0
Order By: Relevance
“…The slight reduction in generalized heritability from the general analysis to the seasonal analyses (Figure 3) occurred due to the smaller number of environments -thus, information -in the former. Nevertheless, the values for this parameter are consistent with the ones normally found in the literature for tropical maize (Dias, Gezan, Guimarães, Nazarian, et al, 2018;Cantelmo et al, 2017;Pereira et al, 2022). By concomitantly analysing the generalized heritability and experimental coefficient of variation values, we verified that there was high experimental precision, which grants credibility to the results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The slight reduction in generalized heritability from the general analysis to the seasonal analyses (Figure 3) occurred due to the smaller number of environments -thus, information -in the former. Nevertheless, the values for this parameter are consistent with the ones normally found in the literature for tropical maize (Dias, Gezan, Guimarães, Nazarian, et al, 2018;Cantelmo et al, 2017;Pereira et al, 2022). By concomitantly analysing the generalized heritability and experimental coefficient of variation values, we verified that there was high experimental precision, which grants credibility to the results.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we applied FAST in a late-stage dataset of tropical maize evaluated in a target population of environments in two crop seasons with distinct environmental conditions. The first season, or summer season, tends to have longer photoperiod, higher water availability and higher solar radiation, which are considered optimal conditions for maize cultivation (Cantelmo et al, 2017). This season spans from September to December and is characterized by favourable weather for sowing depending on the climate zone (F. S. Dias et al, 2019).…”
Section: Core Ideasmentioning
confidence: 99%
“…They concluded that GP is a useful approach for identifying the most informative genotypes. Cantelmo et al (2017) also reported a satisfactory correlation (0.53) between the GEBVs of 402 maize hybrids predicted in the winter crop season and their mean values observed in the summer crop season for grain yield. They also reported that the coincidence index of genomic values of the winter and summer seasons was more efficient to discard the 20% lowest-yielding hybrids (coincidence of 89%) than to select the highest-yielding hybrids (coincidence of 43%).…”
Section: Genomic Prediction For Inducer Developmentmentioning
confidence: 69%
“…Genotyping based on DArT and GBS SNPs has been extensively applied in the association mapping of different crops (e.g., maize, common bean and wheat) (Ates et al, 2018;Cantelmo et al, 2017;Gowda et al, 2015;Ovenden et al, 2017), and in the present study, we compared the results obtained using these two approaches. After appro- Although in the present study we succeeded in narrowing the region corresponding to the major QTL in bin 8.03 compared with previous studies, we still identified 45 hypothetical genes with known predicted functions within this region, which is substantially higher than the 25 hypothetical genes with known predicted functions identified in bin 8.03 by Cao et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping based on DArT and GBS SNPs has been extensively applied in the association mapping of different crops (e.g., maize, common bean and wheat) (Ates et al, 2018; Cantelmo et al, 2017; Gowda et al, 2015; Ovenden et al, 2017), and in the present study, we compared the results obtained using these two approaches. After appropriate filtering, 7258 and 232,801 high‐quality SNPs were retained for DArTseq‐based and GBS‐based association mapping of CML populations, respectively, with the same phenotypic datasets and threshold P value of −log 10 P = 4.53.…”
Section: Discussionmentioning
confidence: 99%